Efficacy and safety of administering pediatric treatment to adolescent patients with mature B‐cell non‐Hodgkin lymphoma within the Japanese Pediatric Leukemia/Lymphoma Study Group clinical trial. Issue 8 (10th April 2018) - Sekimizu, Masahiro; Hashimoto, Hiroya; Mori, Tetsuya; Kobayashi, Ryoji; Horibe, Keizo; Tsurusawa, Masahito
Abstract: Background: Currently, there is no standardized treatment for adolescents, aged 15 years or older, with mature B‐cell non‐Hodgkin lymphoma (B‐NHL), although this age group has been reported to have a poorer prognosis than younger patients. Procedure: The present study analyzed the data of 321 patients with B‐NHL, enrolled in a pediatric clinical trial, comparing the treatment outcomes between adolescents (aged 15–18 years, n = 25) and children (≤15 years, n = 297), with a particular focus on the safety and tolerability of administering pediatric regimens to adolescents. Results: The probability of event‐free survival (EFS) at 4 years was 79.3 ± 8.3% for the adolescents and 88.0 ± 1.9% for the children ( P = 0.236). After adjusting for treatment group and lactate dehydrogenase value at the time of diagnosis, the probability of 4‐year EFS of adolescents was lower than that of children, but only in the patients with central nervous system positive lymphoma or Burkitt leukemia. The frequency of treatment‐related mortalities, severe adverse events (SAEs), and SAEs leading to treatment discontinuation or treatment completion rate was similar in adolescent and pediatric patients. There was no difference in treatment duration between adolescent and pediatric patients. Conclusions: The treatment outcomes of adolescents with B‐NHL were not statistically different from those of the pediatric patients and the safety of a pediatric regimen in adolescents was similar to that in the pediatric patients. A pediatric treatment foundation can be adopted for adolescents, although further prospective studies and biological investigations are required for treatment optimization.